Cultivation of Pleurotus ostreatus on Agricultural Wastes and Their Combination - Bulti Kumera Fufa; Belsti Atnkut Tadesse; Mestawot Merid Tulu (International Journal of Agronomy)
Background. Mushrooms are increasingly becoming an important component of diets worldwide, and it is of paramount importance to choose appropriate substrates to grow them. The objective of this study was to grow Pleurotus ostreatus mushroom using different agricultural substrates. Methods. Corncobs, finger millet straw, and bamboo waste were collected from different sites of the Awi Zone. The substrates were chopped into small pieces, and 500 g of their dry mass alone and their combination was measured, packed in a polythene bag, moistened, and pasteurized. The cooled substrates were inoculated with a spoon of P. ostreatus spawn brought from Debre Berhan University. The bags were placed in the growing room, and growth parameters were recorded continuously with environmental variables. The experimental setup was a complete randomized design, six treatments with three replicates. Results. The fastest spawn running phase of P. ostreatus was 28.71 ± 0.80 days, pinhead formation was 32.36 ± 0.26 days, and fruiting bodies’ formation was 5.19 ± 0.74 days after the pinhead was recorded on the corncob substrate. The highest fresh weight and biological efficiency with the significant statistical association were obtained from P. ostreatus grown on finger millet straw (253.07 ± 1.05 and 50.20 ± 0.47, respectively). The highest average number of pinheads and fruiting bodies (29.60 and 11.44, respectively) was recorded on finger millet straw. The lowest biological efficiency (20.80 ± 0.41), fresh weight (101.48 ± 0.91), number of pinheads (14.40), and number of fruiting bodies (4.25) were recorded from a mixture of corncob and bamboo waste (50% each) substrates. Conclusion. Finger millet straw is recommended as the best substrate for the cultivation of P. ostreatus. The mixed substrate of corncob and bamboo waste (1 : 1) for P. ostreatus cultivation is not encouraged due to poor growth performance.